A Case of Cognitive Decline Resulting from Aging, Temporal Lobe Epilepsy, and Environmental Factors. (10th December 2019) - Veluri, Nikhila
Abstract : Cognitive functioning is imperative in our daily lives. It allows us to understand, process, and react appropriately to different situations. Aging has been linked to cognitive decline. The degree and rate of cognitive decline are crucial as they differentiate normal aging from dementia or memory loss secondary to medical conditions. A 63-year-old Caucasian woman with a 50-year history of temporal lobe epilepsy experienced memory difficulties in recent years. She was admitted voluntarily to the neuropsychiatry ward for a 3-day ambulatory electroencephalogram (EEG), which reported mild bitemporal structural or functional abnormality. The patient reported subjective seizure experiences that were not reflective of seizure activity on the EEG. Possible causes included panic attacks or other anxiety experiences. Routine laboratory test and magnetic resonance imaging results were unremarkable. During her hospital stay she showed improvement in cognitive functioning. However, anxiety continued to negatively impact her memory. We hypothesized that the memory impairments could have resulted from age, psychological factors, the patient's own expectations, pressure from the environment and history of TLE. We diagnosed the patient with mild cognitive impairment and adjustment disorder with anxiety. She was discharged with seizure and anxiety medication. This report highlights the importance of both age-related and disease-related variables when diagnosing patients with cognitive decline.